'I still desire to have a child': a qualitative analysis of intersectional HIV- and childlessness-related stigma in rural southwestern Uganda. Issue 2 (1st February 2023) - Pratt, Madeline C.; Owembabazi, Moran; Muyindike, Winnie; Kaida, Angela; Marrazzo, Jeanne M.; Bangsberg, David R.; Bwana, Mwebesa B.; Psaros, Christina; Turan, Janet; Atukunda, Esther C.; Matthews, Lynn T.
Abstract: This study explored the intersecting forms of stigma experienced by HIV-serodifferent couples with unmet reproductive goals in rural Uganda. The parent mixed-methods study, which included 131 HIV-exposed women with plans for pregnancy, offered comprehensive HIV prevention counselling and care over a nine-month period. In-depth interviews were conducted with 37 women and seven male partners to explore care experiences and the use of safer conception strategies. This secondary analysis explored how challenges conceiving informed pregnancy plans and HIV prevention behaviours. The following themes were developed (1) partnership conflicts arise from HIV- and infertility-related forms of stigma, contributing to gender-based violence, partnership dissolution and the pursuit of new partners; (2) cultural and gender norms pressure men and women to conceive and maintain partnerships, which is complicated by the stigma directed towards serodifferent couples; (3) frustration with low partner participation in safer conception strategies led to the decreased use of these methods of HIV prevention; (4) health care provider support promotes continued hope of conception and helps overcome stigma. In HIV-affected partnerships, these intersecting forms of stigma may impact HIV prevention. Seeking to fulfil their reproductive needs, partners may increase HIV transmission opportunities as they engage in condomless sex with additional partners and decrease adherence to prevention strategies. Future research programmes should consider the integration of fertility counselling with reproductive and sexual health care.